2015
DOI: 10.1109/jsen.2015.2429674
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a Multiple Traffic Parameter Detection Sensor Developed With Quantum Tunneling Composites

Abstract: Quantum tunneling composites (QTCs) are extremely sensitive to external force due to the quantum tunnel effect and have been developed into various sensors used in many fields, such as force sensors and tactile sensors. In this paper, a new type of traffic detection sensor is developed based on QTCs which are fabricated by adding spiky spherical nickel powders as functional fillers into silicone rubber. The developed sensors with different sensitivities were incorporated in an experimental road and a real road… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This has led to the development of various traffic sensors with various sensing principles such as optical sensors, acoustic sensors, magnetic sensors and pressure-sensitive sensors [1][2][3] . Over the last few decades there has been a huge interest in using pressure-sensitive composites for fabricating traffic sensors due to the advantages of simple structures, enhanced properties, versatile surveillance and robust multifunctional applications [2,[4][5][6] . The pressure-sensitive composite refers to a system composed of insulating or semi-conducting matrix (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to the development of various traffic sensors with various sensing principles such as optical sensors, acoustic sensors, magnetic sensors and pressure-sensitive sensors [1][2][3] . Over the last few decades there has been a huge interest in using pressure-sensitive composites for fabricating traffic sensors due to the advantages of simple structures, enhanced properties, versatile surveillance and robust multifunctional applications [2,[4][5][6] . The pressure-sensitive composite refers to a system composed of insulating or semi-conducting matrix (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of the FAQTCs as chemical sensors responding to volatile organic compounds have also been reported [23,24] . Recently, our group has designed and implemented a traffic sensor based on the FAQTCs for long-term and real-time traffic parameter detection [6] . However, these applications usually use the FAQTCs as "all or nothing" switches.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation procedures for composites of two types of rubber matrixes were same. The weight ratio of nickel powder to silicone rubber was chosen as 3:1, according to the [6,14]. The used molds had two different effective depths of 1 mm and 2 mm.…”
Section: Composite Preparationmentioning
confidence: 99%
“…The subsequent researches indicated that QTCs have such merits as extremely high sensitivity, superior robustness, excellent flexibility, and cushioning capability to impact load due to their rubber matrix, which all together enable QTCs with the possibility of applications to many sensing fields. So far, QTCs have been developed into various sensors, such as strain sensors, tactile sensors, gas sensors, and traffic parameter detection sensors [6][7][8][9][10][11][12][13]. However, to the best of our knowledge, no work has been done on the use of QTCs for ship-bridge collision monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The objective was to install embedded sensors with the potential to detect damage inside the structure under real conditions and with real traffic. In the field of traffic detection, new types of embedded sensors such as self-sensing concrete sensors, ceramic sensors and pressure-sensitive detectors are under study [5][6][7], in order to deal with the limitations of traditional inductive loops and of more recent technologies such as microwave radars, infrared sensor, or video image processors. In the extension of these embedded sensors that are able to detect a vertical loading, our study evaluates the ability of embedded sensors to detect internal cracking.…”
Section: Objective: a Communicating Roadmentioning
confidence: 99%